The analysis and application of biomarkers - Grice, Kliti; Eiserbeck, Christiane (Elsevier Science, 2013)
Biomarkers (molecular fossils) are derived from lipids and photosynthetic pigments from organisms that lived long ago in the past. In sedimentary systems, lipids can be reduced to biomarkers. Biomarkers can exist in sediments and oils over hundreds of millions of years. Many of the biomarkers encountered in sediments and oils have been related to lipids of present-day biological systems, thus allowing their biomarker–precursor relationships to be established. They span the three domains of life: eukaryotes, bacteria, and archaea. This chapter represents a summary of biomarkers with respect to their origin (age), reconstructing environments of deposition and their association with some of the largest extinction events of the geologic past. The outlook includes analytical techniques recently employed to analyze biomarkers using, for example, 2D chromatographic techniques and other state-of-the-art mass spectrometry and various pyrolysis techniques.